Chronic hypertension and adverse pregnancy outcome: a cohort study. (22nd June 2017) - Panaitescu, A. M.; Syngelaki, A.; Prodan, N.; Akolekar, R.; Nicolaides, K. H.
ABSTRACT: Objective: To examine the association between chronic hypertension (CH) and a wide range of adverse pregnancy outcomes after adjustment for confounding factors in obstetric history and maternal characteristics. Methods: This was a prospective screening study for adverse pregnancy outcomes in women with singleton pregnancy attending their first routine hospital visit at 11 + 0 to 13 + 6 weeks' gestation. Data on maternal characteristics, medical and obstetric history and pregnancy outcome were collected. Regression analysis was performed to examine the association between CH and adverse pregnancy outcomes, including late miscarriage, stillbirth, pre‐eclampsia (PE), gestational diabetes mellitus (GDM), spontaneous and iatrogenic preterm birth (PTB), small‐for‐gestational‐age (SGA) neonate, large‐for‐gestational‐age (LGA) neonate and elective and emergency Cesarean section (CS). Results: The study population of 109 932 pregnancies included 1417 (1.3%) women with CH. After adjusting for potential confounding variables from maternal characteristics, medical and obstetric history, CH was associated with increased risk of stillbirth (odds ratio (OR), 2.38 (95% CI, 1.51–3.75)), PE (OR, 5.76 (95% CI, 4.93–6.73)), SGA (OR, 2.06 (95% CI, 1.79–2.39)), GDM (OR, 1.61 (95% CI, 1.27–2.05)), iatrogenic PTB < 37 weeks (OR, 3.73 (95% CI, 3.07–4.53)) and elective CS (OR, 1.79 (95% CI, 1.52–2.11)), decreased risk of LGA (OR, 0.65 (95% CI, 0.53–0.78)) and had no significant effect on late miscarriage, spontaneous PTB or emergency CS. Conclusion: CH should be combined with other maternal characteristics and medical and obstetric history when calculating an individualized adjusted risk for adverse pregnancy complications. CH increases the risk of stillbirth, PE, SGA, GDM, iatrogenic PTB and elective CS and reduces the risk for LGA. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.